Relationship between sleep quality, sleep duration, heart rate, and step counts in young adults - Alanur Kara; Halime Arıkan (Turkish Journal of Kinesiology)
It was aimed to explore the connections among sleep quality, heart rate, sleep duration, quality of life, and step count in young adults. The study involved 116 young adults, comprising 61 women and 55 men. Sleep quality was evaluated using the Pittsburgh Sleep Quality Index (PSQI), and sleep duration, heart rate, step count, and energy expenditure were monitored with the Fitbit® Inspire 2. Quality of life was evaluated using the Nottingham Health Profile (NHP) Questionnaire. Correlation analysis was performed using either Pearson or Spearman correlation analysis. The study found no significant relationships between sleep quality, sleep duration, heart rate, and step count (p< 0.05). A very strong positive correlation was found between sleep score and both time asleep (r = 0.730) and REM sleep (r = 0.743), as well as a strong correlation with deep sleep (r = 0.454). Time asleep had very strong positive correlations with REM sleep (r = 0.611) and light sleep (r = 0.782), and strong correlations with awake time (r = 0.438) and deep sleep (r = 0.466). Awake time and light sleep also showed a strong correlation (r = 0.585). Additionally, step count was strongly correlated with energy expenditure (r = 0.519), and a very strong correlation was observed between the section 1 score of the NHP and the PSQI (r = 0.649). These outcomes underscore the complex interplay between sleep and physical activity and emphasize the importance of considering multiple factors when assessing health and quality of life.